Pengaruh Sistem Informasi Akuntansi Dan Kompetensi Pengguna Terhadap Kualitas Laporan Keuangan Rumah Sakit Kanker Dharmai - Viona Argaretha; Sairun Simanullang; Morina Barus (Universitas Veteran Bangun Nusantara, 2025)
This research aims to investigate the impact of Accounting Information Systems and User Skills on the Quality of Financial Statements at Dharmais Cancer Hospital. It is crucial for hospitals to ensure strong management of all their activities, especially in regards to financial reporting. A quantitative research approach was adopted, using surveys to gather data. Fifty individuals submitted data using a questionnaire that has been proven to be reliable and valid. The evaluation included traditional assumption checks and multiple linear regression analyses, conducted using SPSS software. The results indicate that the Accounting Information System and User Competency do not have a significant impact on the Quality of Financial Reporting when evaluated separately. However, when considered collectively, both independent variables have a significant impact on the Quality of Financial Reporting, reflected by an R-squared value of 0. This indicates that the Accounting Information System and User Competency together represent 43. 9% of the variations in the Quality of Financial Statements. The leftover 56. One percent of the variation is influenced by additional factors that are not considered in this analysis. After considering the count of independent variables, the Adjusted R-squared value is 0. The number 415 indicates that the regression model sufficiently accounts for 41. 5% of the adjustments in the Quality of Financial Statements. The leftover amount is 58. Five percent is affected by other factors that were not included in this research.